Calprotectin and Intestinal Fatty Acid Binding Protein (I-FABP) Level in Preterm Neonates with Necrotizing Enterocolitis - Ditya Arisanti; Satrio Wibowo; Soemarno Soemarno (Research Journal of Life Science, 2019)
Necrotizing enterocolitis (NEC) is inflammatory state of intestinal tissue which mostly occurred in preterm neonates and associated with ischemia and inflammation. This study was aimed to investigate calprotectin level (inflammatory marker) and intestinal fatty acid binding protein (I-FABP) (ischemia marker) in preterm neonates with NEC. This research was designed as cross sectional which involve 32 preterm neonates divided into 2 groups as follows: NEC group (n=16 subjects) and control group (n=16 subjects). Diagnosis of NEC was established by clinical and radiological signs (abdominal distension and pneumatosis). Fecal calprotectin and urinary I-FABP were measured using ELISA method. Results showed that fecal calprotectin and urinary I-FABP was significantly higher in NEC group as compared to control group (Mann-Whitney test, p<0.05). Both calprotectin and I-FABP was positively correlated with NEC state (Spearman correlation test, p=0.000, r=0.866). Moreover, calprotectin and I-FABP level was positively correlated with grade (Bell’s classification) and type (Gordon’s classification) of NEC (Spearman correlation test, p<0.05). We concluded that calprotectin and I-FABP level was higher in NEC group. Moreover, I-FABP but not calprotectin, were correlated with grade and type of NEC.